2020
DOI: 10.1186/s13756-020-0679-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of methicillin-resistant Staphylococcus aureus clinical strains from the endotracheal tubes of patients with nosocomial pneumonia

Abstract: Background: Among all cases of nosocomial pneumonia, Staphylococcus aureus is the second most prevalent pathogen (17.8%). In Europe, 29.9% of the isolates are oxacillin-resistant. The changing epidemiology of methicillinresistant Staphylococcus aureus (MRSA) nosocomial infections and the decreasing susceptibility to first-line antibiotics leave clinicians with few therapeutic options. The objective of our study was to determine the antimicrobial susceptibility, the associated molecular mechanisms of resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
4
15
0
Order By: Relevance
“…Since each study group consisted of a different number of strains, and these strains differed in their resistance mechanisms, it is difficult to develop a good tool to track the spread of erm genes over the years. However, when analyzing the data presented in the Table 3, it can be concluded that the frequency of genes, especially ermA and ermC, increases with time [4,16,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]36,37,[65][66][67][68][69][70][71]. -: no data, cMLS B : constitutive phenotype of resistance to macrolides, lincosamides and streptogramin B. iMLSB: inductive phenotype of resistance to macrolides, lincosamides, and streptogramin B. MS B : resistance to 14-and 15-membered macrolides and streptogramin B.…”
Section: Modification Of the Target Site Of Macrolide Actionmentioning
confidence: 99%
“…Since each study group consisted of a different number of strains, and these strains differed in their resistance mechanisms, it is difficult to develop a good tool to track the spread of erm genes over the years. However, when analyzing the data presented in the Table 3, it can be concluded that the frequency of genes, especially ermA and ermC, increases with time [4,16,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]36,37,[65][66][67][68][69][70][71]. -: no data, cMLS B : constitutive phenotype of resistance to macrolides, lincosamides and streptogramin B. iMLSB: inductive phenotype of resistance to macrolides, lincosamides, and streptogramin B. MS B : resistance to 14-and 15-membered macrolides and streptogramin B.…”
Section: Modification Of the Target Site Of Macrolide Actionmentioning
confidence: 99%
“…In dermal tissue, MRSA can cause skin, wound and burn infections [9]. Nosocomial pneumonia is an occasional form of MRSA infection [10]. Additionally, a study conducted in Russia showed that the MRSA was proved to cause a fatal community acquired pediatric pneumonia and intensive care unit associated bacteremia [11].…”
Section: Introductionmentioning
confidence: 99%
“… 32 There are also reports of MRSA strains extracted from the tracheal intubation of ICU patients. 33 Other researchers have suggested that the ICU admission history may be a risk factor for MRSA infection. 34 Therefore, active monitoring of MRSA in ICU patients is crucial and must be considered.…”
Section: Discussionmentioning
confidence: 99%